Aplikasi Pembelajaran tentang Ular di Indonesia berbasis Android - Kevin Andrean Mariyono; Gregorius Satia Budhi; Henry Novianus Palit (Jurnal Infra, 2016)
Indonesia is the largest archipelago country in the world. Every island in Indonesia has a variety of different biological. Variety of biological diversity in Indonesia is also one of the largest in the world. Various types of flora and fauna which adorn every island in Indonesia into a separate icon for each island. One of the existing biodiversity in Indonesia is the type of snake. Indonesia has approximately 20% of the snakes scattered in every island. Such varieties include size, color, and the level of spreading in Indonesia. For all sorts of information about the snakes that exist today is still fairly quite minimal. Books that discuss the types of snakes are still relatively minimal. As the smartphone now has become part of every society, the book was gradually being abandoned. Therefore, the objective of this research is to create an application that can help provide information about snakes in Indonesia with more ease.In this research, the creation of applications of learning about snakes in Indonesia based on Android, which is one smartphone operating system that is used in many circles. This app has a feature that can help users, especially information about snakes, handling and handle snake bites, as well as a variety of other additional information.Based on the results of the implementation and testing is done, the application can provide information about snakes accompanied by photographs and spreading displayed with a map, a brief description and video handling snake bites and how to handle, question and answer forum for sharing information, as well as the provision of other additional information. With this application users can use the information to increase knowledge.